Stress-related IBS - K. Outhoff (South African Family Practice)
The gastrointestinal tract is exquisitely sensitive to different physical and psychological stressors. Irritable bowel syndrome (IBS) may be viewed as a disorder caused by stress-induced dysregulation of the complex interactions along the brain-gut-microbiota axis, which involves the bidirectional, self-perpetuating communication between the central and enteric nervous systems, utilising autonomic, psychoneuroendocrine, pain modulatory and immune signalling pathways. An overzealous stress response may significantly alter not only the sensitivity of the central and enteric nervous systems, but also other potentially important factors such as gut motility, intestinal mucosal permeability and barrier functioning, visceral sensitivity, mucosal blood flow, immune cell reactivity and enteric microbiota composition. Symptoms of these (mal)adaptive changes may include constipation, diarrhoea, bloating and abdominal pain, manifesting clinically as IBS. This article briefly reviews the current postulated stress-models of IBS.